2017
DOI: 10.18203/2349-2902.isj20175142
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial comparing low cost vacuum assisted dressings and conventional dressing methods in the management of diabetic foot ulcers

Abstract: INTRODUCTIONIndia, is ranked first in the list of the ten nations most affected with diabetes, foot ulceration is the most common complication, affecting approximately 15% of diabetic patients during their lifetime. This can be attributed to several social and cultural practices such as barefoot walking, inadequate facilities for diabetes care and education, and poor socioeconomic conditions. 1 Diabetic foot ulceration followed by amputation contributes dramatically not only to the morbidity among persons with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…VAC therapy appears to be more efficacious than conventional dressings in the preparation of diabetic ulcers. 23,24 We observed that the patients on VAC therapy had the early appearance of granulation tissue as compared to the patients treated by moist saline gauze dressings. Complete (100%) granulation was achieved earlier and in a higher proportion of patients in group A as compared to group B.…”
Section: Discussionmentioning
confidence: 90%
“…VAC therapy appears to be more efficacious than conventional dressings in the preparation of diabetic ulcers. 23,24 We observed that the patients on VAC therapy had the early appearance of granulation tissue as compared to the patients treated by moist saline gauze dressings. Complete (100%) granulation was achieved earlier and in a higher proportion of patients in group A as compared to group B.…”
Section: Discussionmentioning
confidence: 90%